Soft-Dielectron Excess in Proton-Proton Collisions at s =13 TeV - Acharya, S.; Adamovã, D.; Adler, A.; Adolfsson, J.; Aggarwal, M.M.; Aglieri Rinella, G.; Agnello, M.; Agrawal, N.; Ahammed, Z.; Ahmad, S.; Ahn, S.U.; Akbar, Z.; et al. (American Physical Society, 2021)
A measurement of dielectron production in proton-proton (pp) collisions at √s = 13 TeV, recorded with the ALICE detector at the CERN LHC, is presented in this Letter. The data set was recorded with a reduced magnetic solenoid field. This enables the investigation of a kinematic domain at low dielectron (ee) invariant mass mₑₑ and pair transverse momentum pₜ,ₑₑ that was previously inaccessible at the LHC. The cross section for dielectron production is studied as a function of mₑₑ, pₜ,ₑₑ, and event multiplicity dNch/dη. The expected dielectron rate from hadron decays, called hadronic cocktail, utilizes a parametrization of the measured η/π⁰ ratio in pp and proton-nucleus collisions, assuming that this ratio shows no strong dependence on collision energy at low transverse momentum. Comparison of the measured dielectron yield to the hadronic cocktail at 0.15 < mₑₑ < 0.6 GeV/c² and for pₜ,ₑₑ < 0.4 GeV/c indicates an enhancement of soft dielectrons, reminiscent of the “anomalous” soft-photon and soft-dilepton excess in hadron-hadron collisions reported by several experiments under different experimental conditions. The enhancement factor over the hadronic cocktail amounts to 1.61 ± 0.13 (stat) ± 0.17 (syst, data) ± 0.34 (syst, cocktail) in the ALICE acceptance. Acceptance-corrected excess spectra in mₑₑ and pₜ,ₑₑ are extracted and compared with calculations of dielectron production from hadronic bremsstrahlung and thermal radiation within a hadronic many-body approach.
Keywords: Proton; Physics; Nuclear physics; https://purl.org/pe-repo/ocde/ford#1.03.00